2010
DOI: 10.1002/cncy.20058
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy and limitations of fine‐needle aspiration cytology of bone and soft tissue lesions

Abstract: BACKGROUND: Fine-needle aspiration (FNA) cytology is increasingly being used as a diagnostic modality for soft tissue and bone lesions. These diagnoses can be challenging because of a variety of factors, including interpretation and sampling issues. This study investigates the diagnostic utility of FNA biopsy, in addition to the diagnostic pitfalls, in soft tissue and bone cytopathology. METHODS: We retrospectively reviewed the soft tissue and bone FNAs over a 4-year period (2004)(2005)(2006)(2007)(2008), alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
60
2
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 30 publications
6
60
2
2
Order By: Relevance
“…When compared with open biopsy, this procedure is well-tolerated by patients and risk of complications is minimal, in addition, the multiple passes of the needle make it possible to sample different parts of a tumor, opposed to a single small core biopsy or open biopsy. [1,2] An almost equal incidence of benign and malignant cases in our series was in contrasting to Rekhi et al, where sarcomas formed a greater proportion of referral cases at their center. [2] In terms of diagnostic efficacy, in malignant cases, we had a sensitivity of 84.61% and specificity of 85.71%.…”
Section: Discussioncontrasting
confidence: 54%
See 3 more Smart Citations
“…When compared with open biopsy, this procedure is well-tolerated by patients and risk of complications is minimal, in addition, the multiple passes of the needle make it possible to sample different parts of a tumor, opposed to a single small core biopsy or open biopsy. [1,2] An almost equal incidence of benign and malignant cases in our series was in contrasting to Rekhi et al, where sarcomas formed a greater proportion of referral cases at their center. [2] In terms of diagnostic efficacy, in malignant cases, we had a sensitivity of 84.61% and specificity of 85.71%.…”
Section: Discussioncontrasting
confidence: 54%
“…Finding a threshold whereby sensitivity is maximized, and inadequacy rates are minimized is hard to define. [1] It has been seen that benign lesions are more difficult to subclassify than malignant lesions. 10 (71%) were subclassified as sarcoma while in contrast, only 7 (53%) could be subclassified as a specific benign lesion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Krishnappa et al 2016 [16] reported two cases of chondroblastoma. Rajani et al 2014 [17] accounted for 2.3% and Khabuss et al 2010 [18] accounted for one case in their study. Osteosarcoma was the most common malignant lesion in our study.…”
Section: Discussionmentioning
confidence: 99%